2018
DOI: 10.1007/s10903-018-0744-3
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Services Utilization Among Migrants in Portugal: Results From the National Health Survey 2014

Abstract: Migrants' health is attracting substantial global interest. We aimed to identify barriers and differences in healthcare services utilization between migrants and natives in a nationally representative sample using data from the National Health Survey 2014. A total of 18,165 participants providing information on country of birth and nationality were included, and comparison of healthcare services utilization was made by using participants born in Portugal and with Portuguese nationality as the reference group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Those respondents who expressed lower self-rated health and/or existing long-term health problems were more likely to experience unmet need for care. This is in line with previous research done in Finland 33,34 and in other countries 3,30 . In addition to health-related factors, only younger age increased the odds for unmet need for care in the nal model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Those respondents who expressed lower self-rated health and/or existing long-term health problems were more likely to experience unmet need for care. This is in line with previous research done in Finland 33,34 and in other countries 3,30 . In addition to health-related factors, only younger age increased the odds for unmet need for care in the nal model.…”
Section: Discussionsupporting
confidence: 93%
“…Variation between different groups of PFB was also found in the study. 29 PFB that have experienced unjust treatment in medical settings often have fewer medical visits, particularly in relation to preventive care 1,30 , and lower attendance to health screenings 31 . A study about childhood cancer mortality and survival among immigrants in Finland showed that patients of foreign background have higher mortality rates compared to those of Finnish background.…”
Section: Introductionmentioning
confidence: 99%
“…Migrants' health in Portugal illustrates another aspect of inequality, which translates into migrants using less and reporting more access restrictions (59). Although COVID-19 morbidities and fatalities by immigration status are not available yet, probably existing inequalities will be exacerbated in the present context.…”
Section: Addressing Health Inequalities In Portugalmentioning
confidence: 99%
“…Also, it is important to know that municipalities with high concentrations of migrants record population density above the national level. For example, the municipality of Amadora, in the Metropolitan Area of Lisbon, which is known to have one of the largest migrant populations in the country, namely, in the neighborhood of The Bairro da Cova da Moura, is recording the highest population density in the entire country with almost 8000 inhabitants per square kilometer (59), in comparison to the average national population density of 111.5 inhabitants per square kilometer (61). Moreover, the same municipality of Amadora, is currently recording the highest number of new confirmed cases per 10,000 inhabitants above the national average (11.1 new cases per 10,000 inhabitants), followed by municipalities in the same Metropolitan Area of Lisbon as follows: Loures (10.0), Odivelas (7.4), Sintra (5.8), and Lisbon (4.9), which are also known to have high concentrations of migrants.…”
Section: Addressing Health Inequalities In Portugalmentioning
confidence: 99%
See 1 more Smart Citation